Continuous overexpression of thioredoxin 1 enhances cancer development and does not extend maximum lifespan in male C57BL/6 mice. Issue 1 (1st January 2018) - Flores, Lisa C.; Roman, Madeline G.; Cunningham, Geneva M.; Cheng, Christie; Dube, Sara; Allen, Colton; Van Remmen, Holly; Hubbard, Gene B.; Saunders, Thomas L.; Ikeno, Yuji
ABSTRACT: We examined the effects of continuous overexpression of thioredoxin (Trx) 1 on aging in Trx1 transgenic mice [Tg( TXN ) +/0 ]. This study was conducted to test whether increased thioredoxin expression over the lifespan in mice would alter aging and age-related pathology because our previous study demonstrated that Tg(act- TXN ) +/0 mice had no significant maximum life extension, possibly due to the use of actin as a promoter, which may have resulted in loss of Trx1 overexpression during aging. To test this hypothesis, we generated new Trx1 transgenic mice using a fragment of the human genome containing the TXN gene with an endogenous promoter to ensure continuous overexpression of Trx1 throughout the lifespan. Universal overexpression of Trx1 was observed, and Trx1 overexpression was maintained during aging (up to 22–24 months old) in the Tg( TXN ) +/0 mice. The levels of Trx1 are significantly higher (approximately 4 to 31 fold) in all of the tissues examined in the Tg( TXN ) +/0 mice compared to the wild-type (WT) littermates. The overexpression of Trx1 did not cause any changes in the levels of Trx2, glutaredoxin, glutathione, or other major antioxidant enzymes. The survival study demonstrated that male Tg( TXN ) +/0 mice slightly extended the earlier part of the lifespan compared to WT littermates, but no significant life extension was observed over the lifespan. The cross-sectional pathological analysis (22–25 months old) showed that Tg( TXN ) +/0 mice had a significantly higher severity of lymphoma and more tumor burden than WT mice, which was associated with the suppression of the apoptosis signal-regulating kinase 1 (ASK1) pathway. Our findings suggest that the increased levels of Trx1 over the lifespan in Tg( TXN ) +/0 mice showed some beneficial effects (slight extension of lifespan) in the earlier part of life but had no significant effects on median or maximum lifespans, and increased Trx1 levels enhanced tumor development in old mice.